CRYPTOGRAPHIC SOUND SAFETY DATA WITH RC4 ALGORITHM - Muhdary A Rahman; Harryanto Theho (Sean Institute, 2019)
Data security and confidentiality is one of the most important aspects in the field of communication, especially communication using computer media. One area of science used to secure data is cryptography. Cryptography is a science that uses mathematical equations to process the encryption and decryption of data. Encryption is the process of changing plaintext (data that can be read) into ciphertext (data that cannot be read) and decryption is the opposite of encryption, which changes ciphertext back into plaintext.